Jednak ostrogi – brązowe okucia typu lutomierskiego w świetle najnowszych badań na cmentarzysku w Ciepłem, gm. Gniew. - Ratajczyk, Zdzisława (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The new investigations into the early medieval cemetery in Ciepłe, Gniew community, uncovered many graves, including three of mounted warriors, in 2009. Their rich grave goods included weapons, horse riding gear, and harness elements. In one of the graves, special attention was attracted by decorative bronze spurs preserved intact. They were found next to the deceased’s feet together with a set of buckles, leather-strap tips and other ferrules. The discovery of these exclusive spurs was a ‘turning point’ in the interpretations of the function of the so-called Lutomiersk-type ferrules.